ANALISIS PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI - Gusmita Sukma Sari.S; Sumarno Sumarno; Almasdi Syahza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of entrepreneurial knowledge on the entrepreneurial interest of students of Economic Education, Faculty of Teacher Training and Education, University of Riau. The population used in this study were students of economic education class 2017, 2018, and 2019. Data collection techniques were carried out by means of documentation to obtain students' entrepreneurial knowledge and using questionnaires to obtain data about interest in entrepreneurship. The samples taken were at least 146 students from 228 students, using the Slovin formula to determine the number of samples used. The data collected was then tabulated and analyzed using chi square. The results showed the value of Asymp. Sig. (2-sided) of 0.000. This value is smaller than 0.05. So it can be concluded that there is an influence of entrepreneurial knowledge on the entrepreneurial interest of students in Economics Education Faculty of Teacher Training and Education, University of Riau.Key word: Entrepreneurial Knowledge, Entrepreneurial Interest.